Analysis Of Eye Fatigue On Medical Record Officers At Hospital X Kupang - Ni'matu Zuliana (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
Technological advances are currently developing very rapidly. Computers are an example of technology that is developing and helping many jobs in various fields, one of which is the hospital. Currently, the recording of patient medical records in several hospitals has switched to using Electronic Medical Records. The development of computerized systems does not always have a positive impact on users, several health problems that often occur, one of which is eye fatigue. The purpose of this study was to analize the factors that cause eye fatigue in medical record officers at X Hospital Kupang. The research design in this study used a descriptive method. The approach used in this study is a cross-sectional design. Sampling with the saturated sample method is to use the entire population. The analysis used univariate to obtain an overview and describe each variable by presenting data using cross-tabulation. The results of the study showed that most of the medical record officers had complaints of severe eye fatigue (45.5%), with an age of < 30 years (60%), duration of work > 2 hours (80%), working time ³ 5 years (60%) and distance from monitor £ 40 cm (60%). Training should be carried out so that employees understand how to work in front of a computer safely Keyword : eye fatigue, computer, medical record